Selective dihydroxylation of methyl oleate to methyl-9, 10-dihydroxystearate in the presence of a recyclable tungsten based catalyst and hydrogen peroxide. (25th June 2020) - Araji, Nahla; Chatel, Gregory; Moores, Audrey; Jérôme, François; De Oliveira Vigier, Karine
Abstract : Synthesis of methyl-9, 10-dihydroxystearate with high yield (99%) from methyl oleate in the presence of hydrogen peroxide and tungsten based catalyst. Abstract : The dihydroxylation of fatty methyl esters is of prime importance for the synthesis of surfactants and lubricants. The conversion of methyl oleate (MO) to 98% yield of methyl-9, 10-dihydroxystearate (MDHS) was performed in the presence of H2 O2 and H3 PW12 O40 catalyst in the absence of a phase transfer agent. The study of the effect of hydrogen peroxide concentration revealed that significant catalytic activity was only achieved for an optimal amount of H2 O2 . A mechanism for this reaction was proposed where hydrogen peroxide reacts with H3 PW12 O40 to produce peroxo-phosphotungstate anions, which directly dihydroxylate MO. The recyclability of the catalyst was also studied. To this aim, a recyclable form of the heteropolyacid was synthesized using Cs cations (Cs2.3 H0.7 PW12 O40 ). This catalyst was recycled up to three cycles without significant loss in catalytic performances.